The evolution of red supergiant mass-loss rates. Issue 1 (11th December 2017) - Beasor, Emma R; Davies, Ben
Abstract: The fate of massive stars with initial masses >8 M⊙ depends largely on the mass-loss rate ($\dot{M}$ ) in the end stages of their lives. Red supergiants (RSGs) are the direct progenitors to Type II-P core collapse supernovae (SNe), but there is uncertainty regarding the scale and impact of any mass-loss during this phase. Here, we used near and mid-IR photometry and the radiative transfer code dusty to determine luminosity and $\dot{M}$ values for the RSGs in two Galactic clusters (NGC 7419 and χ Per) where the RSGs are all of similar initial mass ( M initial  ∼ 16 M⊙ ), allowing us to study how $\dot{M}$ changes with time along an evolutionary sequence. We find a clear, tight correlation between luminosity and $\dot{M}$ suggesting the scatter seen in studies of field stars is caused by stars of similar luminosity being of different initial masses. From our results, we estimate how much mass a 16 M⊙ star would lose during the RSG phase, finding a star of this mass would lose a total of 0.61$^{+0.92}_{-0.31}$  M⊙ . This is much less than expected for $\dot{M}$ prescriptions currently used in evolutionary models.